Growth, survival, nutritional value and metabolism of the sandworm Perinereis quatrefagesi (Grube, 1878) reared in different salinity levels and feed types - Biñas, Joseph B.
Wild-caught juvenile Perinereis quatrefaagesi were reared in three salinity levels (15 ppt, 25 ppt, and 35 ppt) and fed three feed types (fish feces, fish meal and rice bran) for 56 days in two-factorial CRD to determine the effect of diet and salinity to survival, growth, body composition and fatty acid profile of cultured sandworm. Both wild-caught juvenile and adult worms wereexposed to four salinity levels (5 ppt, 15 ppt, 25 ppt and 35 ppt) for 2 hours to determine effect of salinity to oxygen consumption. Survival rates (86+3% to 90+5%) did not vary significantly across all treatments. Growth was not affected by salinity but was influenced by diet with fish meal-fed worms showing higher growth rate (2.2+0.4% day-1) than fish feces-((1.2+0.3 % day-1) and rice bran-fed worms (1.1+0.3 % day-1). Protein contents were similar in all treatments (57.0+2.5 - 68.0+5.3 g100g-1 dw) but fat content was significantly higher in rice bran-fed worms (18.9+1.6 g 100g-1) than in fish feces- (13.6+2.9 g 100g-1 dw) and fish meal fed worms (10.5+3.1 g100-1 dw). Although rice bran-fed worms had significantly high levels of saturated and unsaturated fatty acids, fatty acid profiles of worms in all treatments were comparable. Levels of ARA(0.41+0.21 to 0.89+0.51 g 100g -1 dw), DHA (0.21+0.24 to 0.43+0.22 g 100g-1 dw) and EPA (0.57+0.46 to 0.88+0.31 g 100g-1 dw) did not vary significantly. Weight-specific oxygen consumption by juvenile worms was significantly higher in 5 ppt (88.2+6.4 ug min-1 g-1) and 15 ppt (76.2+7.4 ug min-1 g-1) than in 25 ppt (62.2+7.8 ug min-1 g-1) and 35 ppt (62.8+9.1 ug min-1 g-1). Oxygen consumptions by adult worms in all salinity levels were not significantly different (46.1+3.8 to 59.7+10.5 ug min-1 g-1 ).The study demonstrated that P. quatrefagesi 1) is a good source of protein, lipid and fatty acids ; 2) feeds on feed types with different nutritional qualities and 3) has narrower optimum salinity range as juveniles (25 to 35 ppt) than as adults (5 to 35 ppt). The study also understood the potential of P. quatrefagesi as bioremeditation agent of aquaculture-impacted environments given its ability to ingest both fish feeds and fish waste.